CULTURALLY RESPONSIVE PEDAGOGY: INCORPORATING LOCAL RESOURCES AND INDIGENOUS PRACTICES TO IMPROVE STUDENTS’ ACHIEVEMENT IN SECONDARY SCHOOL CHEMISTRY (UNIZIK Journal of STM Education, 2025)
The study investigated the impact of culturally responsive pedagogy by incorporating local resources and indigenous practices, on students’ achievement in secondary school Chemistry. The study adopted a quasi- experimental design, specifically pretest posttest non -equivalent control group.  Two research questions and three null hypotheses tested at.05 level of significance guided the study. The population of the study comprised 435 (214 male and 221 female) SS1 students in all the public secondary schools in Umuahia North Local Government Area, Abia State. The sample size consisted of 115 (50 male and 65 female) students drawn from the target population using simple random sampling and purposive sampling techniques since gender is a variable in the study. The instrument for data collection, chemistry achievement test (CAT) was face and content validated by three experts in Science Education Department, Michael Okpara University of Agriculture, Umudike. The reliability coefficient of CAT was determined to be 0.74 using Kuder Richardson formula 20 (KR-20). Research questions were answered using mean and standard deviation while the null hypotheses were tested at .05 level of significance using ANCOVA.  The findings of the study indicated a significant difference in students’ achievement between those taught using local resources and indigenous practices and those taught with lecture method, in favour of the experimental group. Again, a non- significant difference in achievement was observed between male and female students exposed to local resources and indigenous practices, and the interaction effect of method and gender was also not significant. It was recommended that chemistry teachers should teach students with materials and examples from their immediate environment to achieve positive results.
Keywords: Local resources, indigenous practices, students’ achievement, Chemistry